Atp7a deficiency induces axonal and myelin developmental defects in zebrafish via ferroptosis - You Wu; Jiahuan Li; Wenya Zhai; Wenye Liu; Hao Wu; Hong Liu; Junxia Min; Fudi Wang; Jing-Xia Liu (Neurobiology of Disease, 2025)
ATP7A genetic mutations lead to Menkes disease (MD), a hereditary neurodegenerative disorder develops significant metabolic abnormalities including copper deficiency and hypomyelination, and even death before 3 years old. However, the underlying mechanisms remain poorly understood. In this study, a dysfunction in axons as evidenced by the shortened axons, reduced branching in each axon, thinner spinal myelin sheaths, and a significant decrease in neuronal membrane potential, was manifested in the central nervous system (CNS) of atp7a−/− larvae. Atp7a is indispensable for the axonal survival in a cell-autonomous manner by fine-tuning copper homeostasis. The transcriptomics analysis identified a significant enrichment of ferroptosis among the differentially expressed genes (DEGs). Iron overload, GPX4 degradation, and lipid peroxidation, the fundamental characteristics of ferroptosis, were evident during atp7a ablation. More importantly, administration of ferroptosis inhibitor Fer-1 or iron chelator DFO, substantially suppressed ferroptosis and largely ameliorated axonal and myelin defects in atp7a−/− larvae. Whereas, larvae exposed to ferroptosis inducer RSL3, and engineered larvae developing ferroptosis, phenocopied the myelin and axonal extension defects observed in atp7a−/− mutants. Taken together, this study highlights the critical importance of atp7a in supporting axonal and myelin development during zebrafish embryogenesis by tightly restraining ferroptosis. This study will shed some light on the theoretical basis and therapeutic targets underlying ATP7A dysfunction induced neurodegenerative diseases.